Nitrogen degradation of the limestone-urea mixtures in the rumen of goats - Harahap, M. A.; Nuswantara, L. K.; Pangestu, E.; Wahyono, F.; Achmadi, J. (Diponegoro University, 2018)
This experiment was aimed to study the degradation kinetics of limestone-urea mixtures in the goats rumen using the nylon bag technique. Samples of limestone were obtained from two limestone mountains, Pamotan Subdistrict of Central Java Province and Wonosari Subdistrict of Yogyakarta Province. The mixtures were created by combining urea at levels 25, 50, 75and 100%; respectively with two limestones on the basis of their Ca contents: L0U100, LP25U75, LP50U50; LP75U25, LW25U75; LW50U50; and LW75U25. The soluble fraction, potentially degradable fraction, the degradation rate of potentially degradable fraction, and effective degradation of respective dry matter (DM) and nitrogen (N) ruminal degradation kinetics were measured in each mixture. The mixture of LP75U25 had lowest effective and degradation rate of potentially degradable fraction (P<0.05) respectively for DM and N compared with those of other mixtures. In conclusion, the limestone-urea mixture of LP75U25 could be suggested as a dietary supplement of ruminal N slow release.